PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK (KAP), DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Siti Lutfiani; Arief Himmawan Dwi Nugroho (Jurnal Riset Akuntansi Politala, 2023)
This study aims to examine and analyze the significance of the variables that influence audit delay in LQ-45 stock companies listed on the Indonesia Stock Exchange.  This study used scientific methods, the population in this study were 52 LQ-45 stock companies listed on the IDX.  The year range used in this study is 3 years, namely 2020-2022.  The sampling technique was purposive sampling and a sample of 25 companies was obtained.  The study used descriptive statistical tests, convergent validity tests, discriminant validity tests, composite reliability tests, Crobsh's Alpha tests, R-Square tests, Fit Model Results, Multicollinearity tests, Multiple linear regression analysis tests, and hypothesis testing with SMART PLS-4 as a processing application.  research data.  The results showed that the variable profitability and firm size had a significant positive effect.  While the Solvency and Auditor Opinion has no significant negative effect, the size of the Public Accounting Firm (KAP) has a significant negative effect.  The ability of the variable profitability, solvency, company size, size of the public accounting firm (KAP) and auditor opinion, in explaining audit delay of 12% is indicated by the adjusted R square of 0.120 while the remaining 88% is explained by other variables outside this research model.